Analisis Pemahaman dan Pelaksanaan Asesmen Nasional pada Guru Matematika Sekolah Menengah di Kecamatan Dampit Kabupaten Malang - Habib Zulfi Abror; Djoko Adi Susilo; Yuniar Ika Putri Pranyata (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Evaluations are carried out by independent institutions periodically, comprehensively, transparently and systematically to assess the achievement of national education standards. The aim of this research is to describe the understanding of secondary school mathematics teachers in the Dampit sub-district regarding the National Assessment system and to describe the implementation of the National Assessment by secondary school mathematics teachers in the Dampit sub-district. This research uses a qualitative approach with a descriptive type. This research was conducted at SMP Negeri 2 Dampit, SMP Diponegoro Dampit, SMAN 1 Dampit, and SMA Diponegoro Dampit, Malang district. Researchers collected data through questionnaires and interviews with mathematics teachers in the schools that were sampled. The results of this research for understanding the national assessment are quite good and its implementation is good, however it should be noted that there are still many obstacles in implementing the national assessment, such as parents of students protesting because their children were not included in the exam during the AN implementation. The government's socialization of the national assessment is not evenly distributed to teachers, so there are still many points in the national assessment that confuse teachers, especially mathematics teachers. Mathematics teachers carry out national assessments based on the principal's instructions, so the socialization from the government has not been felt directly by teachers